1985
DOI: 10.1063/1.336107
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of drawing-induced E′ centers in silica optical fibers

Abstract: The formation mechanism of drawing-induced E′ centers in silica optical fibers is clarified by analyzing the thermodynamic behavior of point defects during the drawing process. The E′ center concentration in the fibers is given by nd=np  exp(−Ef/kTd−A/V1), where Td is the drawing temperature, V1 the drawing speed, and A a constant. The formation energy Ef is 3.8 eV while the precursor concentration np is 7×1022 g−1. The E′ center concentration at the fiber surface is greater than that at the center because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…Furthermore, Photo Luminescence (PL) measurements have demonstrated that some diamagnetic defects such as the Oxygen Deficiency Centre (ODC) may act as defect precursors for paramagnetic defects [7]. These colour defects have been associated with optical absorption bands at short wavelengths below 700 nm [8] and may already be generated during the fiber manufacturing process [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Photo Luminescence (PL) measurements have demonstrated that some diamagnetic defects such as the Oxygen Deficiency Centre (ODC) may act as defect precursors for paramagnetic defects [7]. These colour defects have been associated with optical absorption bands at short wavelengths below 700 nm [8] and may already be generated during the fiber manufacturing process [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…This can cause the redistribution of the material dopants and impurities and, therefore, impact the fiber quality [13,20,22]. The variation of the maximum velocity lag in the neck-down region is shown in Fig.…”
Section: Existence Of Optimal Conditionsmentioning
confidence: 98%
“…The values of the constants are given by Hanafusa et al [20]. For pure silica, the initial concentration of E 0 defects is taken as zero.…”
Section: Analysis and Numerical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of absorption that is believed to take place during fuse propagation was related with Ge' defects, as mentioned above, but also with Si E' defects in the Germanium doped silica core optical fibres. These defects are induced at high temperatures, like the temperatures present in the fibre drawing process (Hanafusa et al, 1985). The E' defects are associated with oxygen vacancies ≡Ge−Si≡ and are stable at temperatures above 870 K. The conjugation of this temperature dependent absorption mechanism with the absorption of the SiO specimen, produced by the thermal decomposition reaction of the Silica glass at high temperatures, occurring for temperatures above 3000 ºC, was considered by Shuto et al to numerically simulate the fuse effect ignition and propagation.…”
Section: Literature Reviewmentioning
confidence: 99%